Utilization of GIS Technology for Mapping Flood-prone Areas in Ambon Island, Indonesia - Heinrich Rakuasa; Viktor Vladimirovich Budnikov (Indonesian Journal of Fundamental and Applied Geography, 2024)
Flooding is one of the most common natural disasters in Indonesia, including on Ambon Island, which can cause significant economic and social losses. This research aims to map flood-prone areas on Ambon Island using Geographic Information System (GIS) technology to map flood hazards and affected residential areas. This research uses variables of elevation, slope, rainfall, land cover, distance from rivers, and soil type. The weighted overlay method was used to produce maps of flood hazards and affected areas. The results showed that the low class flood had an area of 58,114.44 ha, the medium class had an area of 14,066.44 ha, and the high class had an area of 4,733.31 ha, while the built-up land area affected by flooding in the low class had an area of 907.92 ha, the medium class had an area of 3,445.92 ha, and the high class had an area of 1,681.40. The results of this study are expected to make a meaningful contribution to disaster risk management policies on Ambon Island and other areas with similar characteristics.